Principles of Electrical Neural Interfacing A Quantitative Approach to Cellular Recording and Stimulation - Guo, Liang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook fills a gap to supply students with the fundamental principles and tools they need to perform the quantitative analyses of the neuroelectrophysiological approaches, including both conventional and emerging ones, prevalently used in neuroscience research and neuroprosthetics. The content grows out of a course on Neuroengineering and Neuroprosthetics, which the author has taught already several times. The key problems the author addresses include (1) the universal operating mechanisms of neuroelectrophysiological approaches, (2) proper configuration of each approach, and (3) proper interpretation of the resulting signals. Efforts are made both to extract the universal principles underlying this common class of approaches and discern the unique properties of each individual approach. To address these important problems, equivalent electrical circuit modeling and signal analysis are used to unravel the functioning mechanisms and principles and provide sound interpretations to the associated signals and phenomena. This book aims to derive analytical solutions to these equivalent circuits, which can offer clear and complete mechanistic insights to the underlying biophysics. .
Introduction -- Equivalent Circuit Models of Neurons -- Recording Electrodes -- Stimulating Electrodes -- Intracellular Recording -- Extracellular Recording -- Extracellular Recording of Propagating Action Potentials -- Recording using Field-Effect Transistors -- Neural Recording using Nanoprotrusion Electrodes -- Recording using Tetrodes -- Intracortical Functional Neural Mapping Using an Integrated 3D Ultra-Density MEA -- Neuronal Stimulation -- Electrical Stimulation to Promote Neuronal Growth -- Applications.
Keywords: Biomedical engineering; Electronic circuits; Nanotechnology; Biomedical Engineering and Bioengineering; Electronic Circuits and Systems; Nanoengineering; Electrophysiology; Neural stimulation; Neurotechnology (Bioengineering)